"CTBT@20:" an uneasy anniversary. Issue 3 (3rd July 2016) - Istrate, Cristian
ABSTRACT: The June 13, 2016, ministerial meeting of the Preparatory Commission of the Comprehensive Test-Ban Treaty Organization marked the twentieth anniversary of the signing of the treaty and the establishment of the commission. The ministerial sent a strong signal of political support for and commitment to the treaty. Ministers noted with appreciation the organization's achievements related to the detection and deterrence of nuclear-test explosions while also regretting the delay in ratification by the Annex II states. The ministerial emphasized, as the key parameters of the future strategy, the importance of a multilayered approach, including the importance of track-two diplomacy and the use of communication technology that did not exist twenty years ago.